2003
DOI: 10.1037/0735-7044.117.3.485
|View full text |Cite
|
Sign up to set email alerts
|

Age-related deficits in mice performing working memory tasks in a water maze.

Abstract: This study determined whether mice exhibit spatial working memory deficits with increased age. C57BL/6JNia mice of 3 different ages were tested in the Morris water maze with 2 protocols designed to assess immediate and delayed working memory abilities. Young mice required multiple trials in order to show improvements in the working memory task. Deficits in immediate working memory were detected in both 10- and 24- to 26-month-old mice. Reference memory deficits and declines in performance in the delayed workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
46
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 48 publications
12
46
0
1
Order By: Relevance
“…Lack of improvement in the delayed working memory trials was observed only in the case of 26-month old mice. Similar results were obtained in our previous experiment with C57BL/6 mice where middle-aged mice performed well in the delayed working memory trials but the old mice were impaired (Magnusson et al, 2003). To study working memory in rats using the water maze, several investigators have considered using multiple trials within one session to represent working memory (Galea et al, 2000;Kikusui et al, 1999;Lehmann et al, 2000), whereas several others have used only the first trial after a naïve swim (Frick et al, 1995;Morris et al, 1986;Steele and Morris, 1999).…”
Section: Reference and Working Memory Performancesupporting
confidence: 70%
See 1 more Smart Citation
“…Lack of improvement in the delayed working memory trials was observed only in the case of 26-month old mice. Similar results were obtained in our previous experiment with C57BL/6 mice where middle-aged mice performed well in the delayed working memory trials but the old mice were impaired (Magnusson et al, 2003). To study working memory in rats using the water maze, several investigators have considered using multiple trials within one session to represent working memory (Galea et al, 2000;Kikusui et al, 1999;Lehmann et al, 2000), whereas several others have used only the first trial after a naïve swim (Frick et al, 1995;Morris et al, 1986;Steele and Morris, 1999).…”
Section: Reference and Working Memory Performancesupporting
confidence: 70%
“…Frick and coworkers have shown that out of the four trials in working memory tasks, trials 1 and 2 were associated with working memory and trials 4 and 5 were more associated with reference memory (Frick et al, 1995). In our previous experiment we used trial 4 as the delayed trial, but it was not clear if the mice were using working memory for that trial (Magnusson et al, 2003). In the present study we used the second trial (next trial after naïve swim) as the delayed trial (10 minutes delay after naïve swim) and found similar results in both middle-aged and old mice.…”
Section: Reference and Working Memory Performancementioning
confidence: 99%
“…Robust spatial learning impairments in the aged AL rats were evident on all dependent measures during training and the probe test. These results are consistent with much previous research, demonstrating age-related deficits in cognitive function [4,8,36].…”
Section: Discussionsupporting
confidence: 83%
“…Aging rodents have been shown to be a promising animal model for studying memory deficits. In particular, tasks of spatial memory have been employed [1][2][3][4][5][6][7][8] with clearly demonstrated deficits in aged rats as a model associated with aging humans [9][10][11]. Deficits that accompany the decline of spatial learning and memory in aged rats include a loss of visual acuity [12], thermoregulatory control [3], impairments in sensorimotor behavior [6,8,13], and the development of lesions and diseases [14].…”
mentioning
confidence: 99%
“…Age-related changes in complex tasks, such as the spatial version of the water maze, are well documented and have been shown to occur as a function of strain (Gower et al, 1993;Ingram et al, 1999: Frick et al, 2000Magnusson et al, 2003). The wild-type F1 hybrids performed well in all behavioral paradigms evaluated, consistent with hybrid vigor (Owen et al, 1997), and displayed few significant age-related behavioral changes.…”
Section: Discussionmentioning
confidence: 70%